ANTIBACTERIAL ACTIVITY TEST OF THE COMBINATION OF MANGOSTEEN (Garcinia mangostana L.) PERICARP EXTRACT AND CIPLUKAN (Physalis angulata L.) LEAF EXTRACT AGAINST Propionibacterium acnes AS A POSTER DESIGN FOR BIOLOGICAL TECHNOLOGY INNOVATION MATERIALS FOR GRADE X SMA - Chairani Putri; Zulfarina; Darmawati (Yayasan Amanah Nur Aman, 2026)
The problem of acne (Acne vulgaris) is a common skin condition among adolescents and is generally triggered by the growth of Propionibacterium acnes. Various natural-based treatment alternatives have been developed to minimize the side effects associated with chemical agents. Mangosteen (Garcinia mangostana L.) pericarp and ciplukan (Physalis angulata L.) leaves are known to contain diverse secondary metabolites such as xanthones, flavonoids, tannins, saponins, alkaloids, and triterpenoids, which have potential antibacterial properties. This study aims to determine the antibacterial activity of the combined extracts of mangosteen pericarp and ciplukan leaves against Propionibacterium acnes, as well as to develop the research findings into a poster design for the Innovation in Biological Technology learning material for Grade X SMA. The research employed an experimental method using 15 treatment variations of extract combinations. Antibacterial activity was tested using the disk diffusion method on Nutrient Agar medium. Observed parameters included extract yield, phytochemical screening, inhibition zone diameter, and macroscopic and microscopic observations of the test bacteria. The results revealed that both extracts tested positive for active antibacterial metabolites. The antibacterial activity of the extract combinations showed varying inhibition strengths, with several treatments categorized as weak to moderate. The best treatment, P9 (35% mangosteen extract + 35% ciplukan extract), produced a strong inhibition zone measuring 14.14 mm. These findings indicate that the combination of extracts exhibits a synergistic effect in inhibiting the growth of Propionibacterium acnes. The research findings were further developed into a poster design for the Innovation in Biological Technology material for Grade X SMA. Expert evaluations from media and material specialists indicated that the poster is feasible to use as an innovative, informative, and contextual learning medium. The combination of mangosteen pericarp and ciplukan leaf extracts has potential as a natural antibacterial agent for acne control.